Development of a single uredinium inoculation method for Puccinia kuehnii, the causal agent of sugarcane orange rust - Porto,Lis Natali Rodrigues (2018)
ABSTRACT The use of resistant varieties is the ideal method to control rusts. Nevertheless, knowing the pathogen’s diversity is fundamental to the success of this measure. Diversity can be analyzed phenotypically and/or genotypically. For phenotypic diversity, the reaction of genotypes is assessed by means of inoculations of the pathogen generally obtained from several uredinia. One handicap of this technique is its impossibility to detect diversity among these uredinia, assuming that they are all homogenous. Therefore, the aim of the present study was to develop a single uredinium technique for Puccinia kuehnii to be used in studies of rust diversity in sugarcane. The comparison between the two inoculation methods was done by employing urediniospores from SP89-1115 on the varieties SP89-1115 (susceptible) and RB975201 (resistant). The adopted design was completely randomized with five and seven replicates, respectively, examining incubation, latency, disease score, and injured area at 14 and 21 days. The two inoculation techniques were significantly equal for the susceptible variety, considering all evaluated parameters. For the resistant genotype, a significant difference was identified in the injured area and such difference did not interfere in the classification of the reaction of the material since values were below 1%. The single uredinium technique developed in this study showed to be reliable since the genotypic profile of the inoculated fungus was similar to that of pathogens from the produced lesions.